WEB-BASED E-ARCHIVE DATA INFORMATION SYSTEM FOR TEACHERS AND EDUCATION PERSONNEL UPT SDN 1 TAMBAHREJO BARAT - Helinda Agustina (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
In the world of education, archival documentation is very important to manage. This is because at times it is needed for assessment needs, filing and as school history data. The ease and speed of access is greatly supported by various electronic media facilities such as laptops. Increasingly, the development of technology is that almost all schools in big cities are doing archival documentation digitally. This study discusses plans to build a web that contains all the personal documents of teachers and education staff. This research is entitled Information System E-Archive Data for Teachers & Education Personnel UPT SD Negeri 1 Tambahrejo Barat Web-Based. This Web-Based E-Archive Information System was built to make it easier for users to search for personal data information without carrying files that have piled up.